Wireless home networking for dummies - Briere, Daniel D.; Hurley, Patrick J. , 1942- (--For dummies, 2011)
Synopsis: Share stuff safely and wirelessly on Windows PCs or Mac OS X machines. Why go wireless? It's easy, convenient, inexpensive, and, with the emergence of new industry standards, better than ever! These experts know what you should look for (and look out for). They'll walk you through the pros and cons of the different standards, planning and installing your network, setting up security, and getting the most from your investment. Discover how to: Choose the right networking equipment; Integrate Bluetooth into your network; Work with servers, gateways, routers, and switches; Protect your network from intruders; Understand 802.11n